A history of the University of Cambridge. - Searby, Peter (Cambridge University Press, 1997)
Cambridge in the eighteenth and nineteenth centuries was a place of sharp contrasts. At one extreme a gifted minority studied mathematics intensively for the Tripos, the honours degree. At the other, most undergraduates faced meagre academic demands and might idle their time away. The dons, the fellows of the colleges that constituted the University, were chosen for their Tripos performance and included scholars of international reputation such as Whewell and Sidgwick, but also men who treated their fellowships as sinecures. A pillar of the Church of England that denied membership to non-Anglicans, the University functioned largely as a seminary, while teaching more mathematics than theology. This volume describes the complex institution of the University, and also the beginnings of its transformation after 1850 - under the pressure of public opinion and the State - into the University as it exists today: inclusive in its membership, diverse in its curricula, and staffed by committed scholars and teachers.